1969
DOI: 10.1115/1.3571209
|View full text |Cite
|
Sign up to set email alerts
|

Small-Amplitude Frequency Behavior of Fluid Lines With Turbulent Flow

Abstract: The results of semiempirical analytical and experimental studies of the acoustic frequency response of circular tubes with a mean turbulent flow are given. For the frequency range tested, it is seen that the hypothesis of a time-invariant eddy viscosity profile across the tube predicts the behavior well. For lower frequencies a simple lag in the turbulence profile from its equilibrium values is hypothesized which should be of moderate importance in acoustic behavior and of great importance in large-amplitude b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…10 (Loureiro andRamos 2003, Abreu andAlmeida 2004). The k P coefficient can be linked to the momentum correction factor, β, by k P ≈ β−1 for low frequency disturbances (Brown et al, 1969). The coefficient k A may be interpreted as the extra frictional damping due to the unsteady shear stress.…”
Section: Modelmentioning
confidence: 99%
“…10 (Loureiro andRamos 2003, Abreu andAlmeida 2004). The k P coefficient can be linked to the momentum correction factor, β, by k P ≈ β−1 for low frequency disturbances (Brown et al, 1969). The coefficient k A may be interpreted as the extra frictional damping due to the unsteady shear stress.…”
Section: Modelmentioning
confidence: 99%
“…Funk and Wood [1974] utilized a method previously developed for monotonic turbulent flow (Wood and Funk [1970]) to study small amplitude frequency response. It was found that this boundary layer theory was able to reproduce Brown at al's [1969] results excellently. Lu et al [1975] carried out detailed measurements of time-averaged and instantaneous parameters, in pulsating turbulent pipe flow.…”
Section: Conclusion For Monotonically Varying Turbulent Pipe Flowmentioning
confidence: 76%
“…It is only relatively recently that detailed studies of either monotonically varying (Daily et al [1956]) or periodically varying (Brown et al [1969]) turbulent flow have appeared.…”
Section: Unsteadiness In Laminar and Turbulent Pipe Flow -Literatumentioning
confidence: 99%
“…where f is the well-documented friction factor (15). The weighting function w can be approximated by the summation of first-order lag terms in the same way as for laminar flow.…”
Section: Turbulent Frictionmentioning
confidence: 99%